Tectonic Processes and Landforms in the Lesser Himalayas : An experimental study from Khairna Watershed - Joshi, Jyoti (National Geographical Journal of India, 2022)
Different types of landforms and processes in different parts of the earth surface are topic of interest for the people studying geomorphology. Landforms change with time through active processes. The role of these processes becomes very significant when we are concerned with the young and dynamic mountain system like the Himalayas. The changing intensity and speed of processes that are reflected in the landforms of a Himalayan watershed is the topic of interest in this study. Analysis of the tectonically controlled landforms within the watershed further help for a better understanding of sediment mobilization and transportation of earth material down slopes and downstream. Khairna watershed, a Lesser Himalayan drainage basin is used as an experimental laboratory for continuous monitoring of the geomorphologic processes and associated landforms. Field investigations were conducted in the Khairna watershed between 2004-2007.Steep to very steep scarps, terraces, triangular facets, and waterfalls in the study area are associated with the faults and are caused by vertical displacement of rocks due to differential uplift. Apart from direct tectonic origin, debris channels, debris fans and cones, cols and knolls, sudden changes in river profiles are examples of tectonically controlled landforms modified by denudation activities. Identification, monitoring and analysis of different processes and associated landforms in the experimental drainage basin may help to understand the geomorphic processes in a systematic way which affect the region as well as the people living in the region in various ways. Similar studies in different parts of the dynamic Himalayan watersheds may be helpful for the systematic analysis of landforms and the processes associated with their origin to a great extent.